Institutional, supervisory, and personal demands: unravelling the challenge-hindrance demands in doctoral programs - Vrinda Acharya; Ambigai Rajendran; Nandan Prabhu; Aneesha Acharya K (Cogent Education, 2024)
This study elucidates how doctoral students perceive the challenges and impediments of their doctoral programs. In this study, the demands of doctoral programs are characterized as challenges that stimulate students’ potential and hindrances that threaten their well-being. Thirty-five full-time PhD students at various stages of their programme participated in semi-structured interviews as part of a qualitative study. The thematic analysis investigated students’ challenges and hindrances in their programs. Qualitative research identified three themes under challenge and hindrance demands: institutional, supervisory, and personal. The study developed six propositions based on transactional stress theory regarding challenge and hindrance demands. These propositions assist supervisors and doctorate educators in explaining the challenge and hindrance demands framework in a doctoral program context. Demands, such as ambiguity in doctoral research roles, inadequate resources for doctoral programs, and interpersonal conflict, threaten the well-being of doctoral students. Challenge demands such as workload, role responsibility, and role complexity support students’ potential growth and well-being. Furthermore, the present study offers three recommendations for enhancing the doctoral program: establishing an approachable institutional ecosystem, emphasizing the vital role of supervisors, and fostering work-life balance among students.